Hubungan Tingkat Pengetahuan dengan Gaya Hidup pada Penderita Hipertensi di Kelurahan Legok Kota Jambi - Maimaznah, Maimaznah; Hidayat, Muhammad (Prosiding Seminar Kesehatan Nasional, 2024)
Hypertension is persistent blood pressure where the systolic pressure is above 140 mmHg and the diastolic pressure is above 90 mmHg. In the elderly, hypertension is defined as a systolic pressure of 160 mmHg and a diastolic pressure of 90 mmHg. The causes of hypertension include emotional disturbances, obesity, excessive alcohol consumption, excessive stimulation of coffee and tobacco, drugs and heredity. These causes include the influence of lifestyle, while the lifestyle itself is a daily habit, in English "Habits". Habits are anything that a person does on a regular basis or regularly helps shape their unique lifestyle. Hypertension data in Jambi City in 2020 was 18.82% from 20 Puskesmas with male (14.5%) and female (23.17%) divisions, and the Puskesmas that had the highest hypertension cases was Putri Ayu Danau Sipin Health Center which was 4.16 or 51.85%. Putri Ayu Health Center has several target areas, including Legok Village. Legok is located in Lake Sipin District, Jambi City. The results of the assessment of hypertension sufferers obtained in Legok Village include several RTs, namely 35 as many as 22 people, RT 26 as many as 8 people, RT 28 as many as 10 people, RT 38 also as many as 10 people with hypertension. The results of interviews with RT 28 cadres said that 80% of the residents of this RT had hypertension. The purpose of this study was to determine the level of knowledge, lifestyle and the relationship between the level of knowledge and lifestyle in hypertension patients in Legok Village, Jambi City. The method for selecting samples in this study used total sampling with a total sample of 69 people with hypertension. The results showed that there were 35 (50.7%) good knowledge of hypertension patients and a healthy lifestyle in hypertensive patients (52.2%) of 69 respondents. The results of this study indicate that the p-value = 0.37, this indicates that there is no relationship between the level of knowledge and lifestyle in hypertensive patients in Legok Village, Jambi City.